A study on the potential of tsunamigenic earthquakes in Java Subduction Zones. Issue 1 (May 2020) - Fauzi, Y; Hartono,; Kongko, W; Brotopuspito, K S
Abstract: Subduction zone is a source of tectonic earthquakes that has potential to cause a tsunami. The study aims to obtain the estimation of earthquake parameter as a tsunami generator. Earthquake parameters were analyzed by using the scaling law theory for thrust fault type in the subduction zone. This study employed three magnitude scenarios, namely 8.9, 9.0 and 9.2 taken from the National Earthquake Study Center (Pusgen) of Indonesia and Blaser's Equation. The results of model design in a vertical displacement indicated that deformation occurred on the seafloor. The results of source modeling illustrated the variations in maximum vertical displacement values for all three scenarios, namely 4, 123; 5, 309 and 4, 831 meters based on the Blaser's equation and 3, 517; 3, 183 and 4, 526 meters based on the Pusgen's data. The results of the study indicated that the value of vertical displacement can provide an estimate of the tsunami wave height at sea level.